Monitoring Ceftazidime-Avibactam and Aztreonam Concentrations in the Treatment of a Bloodstream Infection Caused by a Multidrug-Resistant Enterobacter sp. Carrying Both Klebsiella pneumoniae Carbapenemase–4 and New Delhi Metallo-β-Lactamase–1. (5th December 2019) - Yasmin, Mohamad; Fouts, Derrick E; Jacobs, Michael R; Haydar, Hanan; Marshall, Steven H; White, Richard; D'Souza, Roshan; Lodise, Thomas P; Rhoads, Daniel D; Hujer, Andrea M; Rojas, Laura J; Hoyen, Claudia; et al.
Abstract: In an infection with an Enterobacter sp. isolate producing Klebsiella pneumoniae Carbapenemase–4 and New Delhi Metallo-β-Lactamase–1 in the United States, recognition of the molecular basis of carbapenem resistance allowed for successful treatment by combining ceftazidime-avibactam and aztreonam. Antimicrobial synergy testing and therapeutic drug monitoring assessed treatment adequacy.